Editorial - Feijoo, Ana Maria Lopez Calvo de; Protásio, Myriam Moreira; Portavales, Victor; Costa, Paulo Victor Rodrigues da (Estudos e Pesquisas em Psicologia, 2020)
Ana Maria Lopez Calvo de Feijoo, Myriam Moreira Protásio, Victor Portavales, Paulo Victor Rodrigues da Costa